Unconventional credit policy in an economy under zero lower bound - Jorge Pozo; Youel Rojas (Graduate Institute of International and Development Studies, 2021)
In this paper we develop a simple two-period model that reconciles credit demand and supply frictions. In this stylized but realistic model credit and deposit markets are interlinked and credit demand and credit supply frictions amplify each other in such a way that produces in equilibrium very low levels of credit and stronger reductions of the real and nominal interest, so an economy is much closer to the ZLB. However, an unconventional credit policy, that consists on central bank loans to firms that are guaranteed by the government, can undo partially the effects of the credit frictions and prevents the economy from reaching the ZLB. Since central bank loans are not subject to the moral hazard problem between bankers and depositors and are government-guaranteed, credit market interventions rise aggregate credit supply and positively affect the aggregate credit demand, respectively. However, once the economy is at the ZLB the effect of a credit policy is reduced due to a relatively stronger inflation reduction, which in turn reduces entrepreneurs' incentives to demand bank loans.
Keywords: G21; G28; E44; E5; 330; Unconventional credit policy; asymmetric information; moral hazard; zero Lower bound